THE INFLUENCE OF TEACHING GAME LEARNING MODEL FOR UNDERSTANDING (TGFU) ON PLAY SKILLS IN LEARNING ON FOOTBALL (Experimental Research at SSB Pro Duta FC) - Fajar Hafian Dani, - (2020)
The main objective in this study is to find out how the application of the TGFU learning model to improving soccer playing skills. Subject The subject of this research was Pro Duta FC Bandung students who were divided into two experimental and control groups. Method. The method in this study uses experimental research with a research design, pre test post test control design. Results. In this study get the data value that the output value of the "Independent Samples Test" output table in the "Equal variances assumed" section is known Sig values. (2-tailed) of 0.001 <0.05, then as the basis for decision making in the independent sample t test, it can be concluded that H0 is rejected and Ha is accepted. Thus it can be concluded that there is a significant (real) difference between the average student learning outcomes in the TGFU group and the control group using direct teaching. Conclusion. From the results of this assessment that there is an increase in each group from the initial test to the final test. Of the two groups, the experimental group was superior to see the average results of this play test. It can be concluded that there is an increase in the use of the TGFU learning model. Keywords : Teaching Game For Understanding, Sepak Bola, learning models.